Comparative Efficacy of Oral Versus Intravenous Antibiotics in the Treatment of Spontaneous Bacterial Peritonitis and Incidence of Antibiotic Associated Acute Kidney Injury - Haider, Ali Saqlain; Ullah, Humaira Sami; Neha Ahuja; ABAD-UR-REHMAN; KASHIF RIAZ; MAHESH KUMAR WADHWA (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Spontaneous bacterial peritonitis is a serious infection that commonly occurs in patients having ascites due to cirrhosis of liver. Antibiotic therapy remains the cornerstone of treatment. The choice between oral and intravenous antibiotics can play a significant role its management outcome. Objective: To compare the efficacy of oral versus intravenous antibiotics in treating spontaneous bacterial peritonitis. Methodology: This prospective study was conducted at Department of Nephrology, University College of Medicine & Dentistry, The University of Lahore from 1st September 2024 to 28th February 2025. One hundred and sixty patients diagnosed with spontaneous bacterial peritonitis were enrolled. Patients were randomized into two groups: oral antibiotic treatment (group A) and intravenous antibiotic treatment (group B). Both groups received antibiotics appropriate for the suspected pathogens. Only uncomplicated SBP patients were included. The primary endpoint was clinical improvement, with secondary endpoints including survival, microbiological resolution, and adverse effects. Results: Both groups showed similar rates in clinical improvement (87.5% in group A vs. 89.2% in group B), survival (80.3% in group A vs. 82.5% in group B), and microbiological resolution (90.2% in group A vs. 92.4% in group B). Adverse effects, including Acute Kidney Injury, were more common in the intravenous group (10% vs. 3.5%). Conclusion: Oral antibiotics appear to be equally effective as intravenous antibiotics for the treatment of uncomplicated spontaneous bacterial peritonitis, with fewer side effects and lower healthcare costs. Intravenous antibiotics should be reserved for critically ill patients or those with severe or complicated infections.